Kualitas Pendidikan Di Afrika Selatan: Antara Kemajuan Dan Ketimpangan - Fahma Aulia; Agus Faisal Asyha (Jurnal Adab dan Peradaban Islam, 2026)
This study aims to analyze the quality of education in South Africa from historical, philosophical, sociological, juridical, curriculum, and governmental and societal perspectives. The method employed was a literature study using a descriptive qualitative approach. Data were collected from scientific journals, books, international reports, and educational policy documents. The findings indicate that South Africa has made significant educational progress since the end of apartheid, particularly in expanding access to education, curriculum reform, and inclusive education policies. However, educational quality continues to face disparities caused by socioeconomic and geographical factors, teacher quality, educational facilities, and technological access. The study concludes that more equitable and sustainable policies are needed to improve educational quality for all members of society.